2019
DOI: 10.1002/path.5266
|View full text |Cite
|
Sign up to set email alerts
|

TET1 reprograms the epithelial ovarian cancer epigenome and reveals casein kinase 2α as a therapeutic target

Abstract: Ten‐eleven translocation methylcytosine dioxygenase‐1, TET1, takes part in active DNA demethylation. However, our understanding of DNA demethylation in cancer biology and its clinical significance remain limited. This study showed that TET1 expression correlated with poor survival in advanced‐stage epithelial ovarian carcinoma (EOC), and with cell migration, anchorage‐independent growth, cancer stemness, and tumorigenicity. In particular, TET1 was highly expressed in serous tubal intraepithelial carcinoma (STI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…[ 12 ] Nevertheless, this study was limited by the fact only TET1 deletion was studied, and thus, the effect of low expression and high expression of TET1 is lacking. Furthermore, a study from Chen et al [ 23 ] showed that TET1 expression correlated with poor survival in advanced-stage epithelial ovarian carcinoma (EOC), as well as cell migration, anchorage-independent growth, cancer stemness, and tumorigenicity. In particular, TET1 was highly expressed in serous tubal intraepithelial carcinoma (STIC), which is currently considered as a type II EOC precursor, and inversely correlated with TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 12 ] Nevertheless, this study was limited by the fact only TET1 deletion was studied, and thus, the effect of low expression and high expression of TET1 is lacking. Furthermore, a study from Chen et al [ 23 ] showed that TET1 expression correlated with poor survival in advanced-stage epithelial ovarian carcinoma (EOC), as well as cell migration, anchorage-independent growth, cancer stemness, and tumorigenicity. In particular, TET1 was highly expressed in serous tubal intraepithelial carcinoma (STIC), which is currently considered as a type II EOC precursor, and inversely correlated with TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, TET1 was highly expressed in serous tubal intraepithelial carcinoma (STIC), which is currently considered as a type II EOC precursor, and inversely correlated with TP53 mutations. [ 23 ] Further, TET1 could activate multiple oncogenic pathways by demethylating the epigenome, including an immunomodulation network having casein kinase II subunit alpha (CK2±) as a hub. [ 23 ] These differences may be as a result of the differing cell origins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OC patients with high expression of Cyclin-dependent kinase 9 (CDK9) in relapsed and metastatic lesions have a worse prognosis than patients with low expression of CDK9 [9]. A number of studies in transcription and epigenetics have confirmed that the occurrence, development, and therapeutic efficacy of OC are influenced by the dynamic changes of multiple oncogenes and tumor suppressor genes [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%